Implementing non-formal education for the locals: the case of Tanah Ombak and fishermen community - Febriany, Sarah (Journal of Sustainability, Society, and Eco-Welfare, 2023)
This study is a program evaluation research conducted in Non-Formal Education by the Tanah Ombak Community. This community is here to change the next generation of Purus (coastal area) to be better, cut off from the poverty chain that has been entangled and free from a marginalized environment. Tanah Ombak non-formal education is a public space for activities in the arts and literacy for school-age children and adolescents in Purus. The goal is for them to leave the "bad habits" that have been a tradition in the Purus community and develop a good character. The evaluation of non-formal education utilized the CIPP (Context-Input-Process-Product) evaluation model and capacity-building analysis of the beneficiaries. The results of this evaluation study show capacity building at the individual level, which is assessed from the aspects of knowledge, skills, attitudes, and behavior. Based on the results of the research evaluation, it was found that non-formal education was able to increase the capacity of participants, as well as change negative behavior. In addition, the results of the CIPP analysis show that Tanah Ombak Non-Formal Education still has shortcomings in its implementation from the Input, Process, and Product aspects in the form of the ability of the issues discussed, facilities, lack of facilitators, and the absence of evaluation-monitoring of the extent to which the objectives have been achieved.